Teams Games Tournament Learning Model with Napier Rods on Mathematics Learning Outcomes for Grade V - Suari, Ni Wayan Mirah Indra; I Wayan Wiarta (Universitas Pendidikan Ganesha, 2025)
The low student learning outcomes in mathematics learning are caused by the lack of innovation learning. The learning used is still conventional learning where students are placed as objects of learning, who do not have the opportunity to develop their thinking skills, as a result students are less actively involved in learning. This study aims to analyze the effect of TGT (Teams Games Tournament) learning model assisted by napier rod media on mathematics learning outcomes of fifth grade elementary school students. This type of research is a quasi-experimental with quantitative methods in the form of post-test only control group design. The study population consisted of 282 students. The sample was selected using cluster random sampling, resulting in an experimental class of 30 students and a control class of 29 students. The data collection method is a test using a multiple choice test instrument. The research data were analyzed with inferential statistical techniques (t-test) polled variance. The results of data analysis obtained that the average post-test score in the experimental class was 88.66 which was in the high category, while the average post-test score in the control class was 70.52 which was in the medium category in the PAP table with a scale of 5 (Five). The results of the t-test analysis obtained tcount = 9.119 and ttable = 2.002 at a significant level of 5% with dk = 57, so that tcount = 9.119> ttable = 2.002 then H0 is rejected and H1 is accepted which means there is a significant difference in math learning outcomes between students who use the TGT learning model assisted by napier rod media and those who do not. It can be concluded that there is a significant effect of the TGT learning model assisted by napier rod media on the learning outcomes of grade V elementary school students.